2020
DOI: 10.3390/ijms21124549
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Evolutionary Adaptation toward Host Entry and Recognition of Receptor O-Acetyl Sialylation in Virus–Host Interaction

Abstract: The recently emerged SARS-CoV-2 is the cause of the global health crisis of the coronavirus disease 2019 (COVID-19) pandemic. No evidence is yet available for CoV infection into hosts upon zoonotic disease outbreak, although the CoV epidemy resembles influenza viruses, which use sialic acid (SA). Currently, information on SARS-CoV-2 and its receptors is limited. O-acetylated SAs interact with the lectin-like spike glycoprotein of SARS CoV-2 for the initial attachment of viruses to enter into the host cells. SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 174 publications
(235 reference statements)
0
70
0
1
Order By: Relevance
“…A study from Baker et al has shown evidence that SARS-CoV2 also binds N-acetylneuraminic acid (Neu5Ac), with this interaction being mediated by the NTD of the S1 subunit ( Baker et al, 2020 ). This is the first in vitro evidence of this occurring, although several prior bioinformatics and modeling studies have hypothesized that a Neu5Ac binding site exists, with one suggesting its affinity for Neu5Ac (0.88) is only slightly lower than that of influenza hemagglutinin (0.94) ( Alban et al, 2020 ; Behloul et al, 2020 ; Fantini et al, 2020 ; Kim, 2020 ; Milanetti et al, 2020 ; Robson, 2020 ). Binding of sialic acids by the NTD is the main entry mechanism in several other coronaviruses known to infect humans, most notably members of the bovine coronavirus family ( Li, 2015 ).…”
Section: Sars-cov2: Host Cell Attachment and Entrymentioning
confidence: 74%
“…A study from Baker et al has shown evidence that SARS-CoV2 also binds N-acetylneuraminic acid (Neu5Ac), with this interaction being mediated by the NTD of the S1 subunit ( Baker et al, 2020 ). This is the first in vitro evidence of this occurring, although several prior bioinformatics and modeling studies have hypothesized that a Neu5Ac binding site exists, with one suggesting its affinity for Neu5Ac (0.88) is only slightly lower than that of influenza hemagglutinin (0.94) ( Alban et al, 2020 ; Behloul et al, 2020 ; Fantini et al, 2020 ; Kim, 2020 ; Milanetti et al, 2020 ; Robson, 2020 ). Binding of sialic acids by the NTD is the main entry mechanism in several other coronaviruses known to infect humans, most notably members of the bovine coronavirus family ( Li, 2015 ).…”
Section: Sars-cov2: Host Cell Attachment and Entrymentioning
confidence: 74%
“…Coronaviruses also have a propensity to bind acetylated sialic acid residues, which are abundant on cell membrane proteins including on megakaryocytes and endothelial cells 20,21 .…”
mentioning
confidence: 99%
“…spikes glycoprotein of all the human coronavirus such as SARS-CoV, HCoV-NL63 and SARS-CoV-2 (COVID-19 virus). The Receptor Binding Domain (RBD) of spike proteins and ACE2 receptors come in direct contact and initiate fusion with cell membrane (Kim, 2020 ; Robson, 2020 ). Since this interaction is essential for SARS-CoV-2 entry into the host cell and infection, this S-RBD–ACE2 interface can be the main target for vaccine developers (Shang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%